Entrepreneurship Development in Islamic Elementary Schools: Supports and Challenges - Nur Kholis; Rizki Ayuningtyas; Muh. Khoirul Rifa'i (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Developing entrepreneurial attitudes and spirit is crucial at an early age. This article aims to analyze the implementation of entrepreneurship programs in improving the student life skills of Islamic Elementary School Sari Bumi Sidoarjo. The data was collected from documents of entrepreneurship program activities and interviews with principals, deputy principals, and the entrepreneurship program manager. The analysis was done by condensing the collected data, presenting the data in a more understandable form, and finally generating a conclusion. Cross-data validation was done based on the data source and collection methods. The results showed that, first, the entrepreneurship programs implemented in this school included business day, product bazaar, business on the road, and entrepreneurial studies, and second, factors supporting the success of the entrepreneurial program are family support, student willingness, available infrastructure, budget, and human resources available in the school. The various entrepreneurship programs are the school’s effort to ensure that its graduates have good life skills in the future. The results of this study indicate the need for the provision of entrepreneurial programs at the elementary school level to ensure that all graduates have basic entrepreneurial knowledge and skills.